2019
DOI: 10.1007/s00167-019-05795-7
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon autograft ACL reconstructed subjects overshoot target knee extension angle during active proprioception testing

Abstract: Purpose To compare the active joint position sense (JPS), muscle strength, and knee functions in individuals who had anterior cruciate ligament (ACL) reconstruction with quadriceps tendon autograft, hamstring tendon autograft, tibialis anterior allograft and healthy individuals. It was hypothesized that when compared to an age and gender‐matched healthy control group, subjects who were post‐ACL reconstruction would display impaired active joint position sense, knee extensor and flexor strength symmetry and kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 41 publications
(73 reference statements)
0
50
0
1
Order By: Relevance
“…The physical activity was not consistently described. Three studies reported a Tegner Score [ 20 , 21 , 24 ] and one stated that the participant groups had the same Tegner Score without the actual number [ 23 ]. Two studies included elite athletes [ 17 , 18 ] and one study nonprofessional athletes [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The physical activity was not consistently described. Three studies reported a Tegner Score [ 20 , 21 , 24 ] and one stated that the participant groups had the same Tegner Score without the actual number [ 23 ]. Two studies included elite athletes [ 17 , 18 ] and one study nonprofessional athletes [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not reported the activity level of the participants [ 7 , 19 , 22 ]. The most reported surgery type was bone patellar tendon bone autograft [ 7 , 18 , 20 22 , 25 ], followed by hamstring tendon autograft [ 7 , 18 , 23 25 ]. Further, it should be noted that different surgery types in the same or in multiple study populations were reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is not without limitations. Guney-Deniz et al 15 demonstrated that a patient who received ACLR with an autograft quadriceps tendon is less likely to correctly identify joint position at 15 of flexion compared to hamstrings or tibialis anterior autografts (P < .0001). When a quadriceps tendon harvest is performed, there is a risk of violating the suprapatellar pouch; however, it should be noted that a disruption of the suprapatellar FiberTag suture is then pierced using the teeth of the GraftClamp.…”
Section: Discussionmentioning
confidence: 99%